Getting Financial Aid 2016 (New York, 2015)
Describes the financial aid opportunities at over three thousand two- and four-year colleges, universities, and technical schools, accompanied by a planning calendar, worksheets, itemized charts, and cost-saving tips.
Keywords: Student aid,Trợ giúp sinh viên; United States,Hoa Kỳ